A case of fungal keratitis due to Fusarium solani after an indigenous healing practice. (2019) - Ortega-Rosales, Alberto; Quizhpe-Ocampo, Yomara; Montalvo-Flores, María; Burneo-Rosales, Carlos; Romero-Ulloa, Gilda
Abstract: Fusarium keratomycosis is a destructive eye infection that is difficult to treat and produces a poor outcome, which can affect healthy patients. Keratomycoses are rare and can be underdiagnosed, thus, direct microscopic examination and culture are essential for an early specific diagnosis and must be taken into consideration to establish the most effective treatment and avoid severe complications. Herein, we present a case of a healthy patient, who was diagnosed with Fusarium solani keratitis. He developed a corneal infection without an obvious history of trauma, and any comorbidity but with a history of contact with juice of herbs during an indigenous healing practice, which was the most likely cause for the development of the fungal infection. He was treated with intrastromal voriconazole and systemic itraconazole, with a good clinical course, however with sequelae of decreased visual acuity.